ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA E-BOOK BERBASIS CANVA PADA MATA PELAJARAN IPA KELAS V DI SEKOLAH DASAR - Kayla, Kayla; Usman, Herlina; Yunus, Mahmud (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to identify the need for developing an e-book using Canva for fifth-grade science learning at SDIT Utsmanil Hakim. The research employed a qualitative descriptive method, with data collected through teacher interviews and student surveys. The e-book development follows the ADDIE model, which includes five stages: Analyze, Design, Develop, Implement, and Evaluate. The interviews revealed that most teachers believe digital learning tools such as e-books are necessary to enhance student engagement and enjoyment in learning science. Teachers also noted that digital media like videos and images help students better understand complex topics such as the water cycle, layers of the Earth, and Earth’s surface. Although e-books have not been widely used, teachers agreed that integrating text, images, videos, and quizzes would make learning more interactive and motivating. Student survey results indicated that most students prefer using e-books and find Canva-based e-books more engaging than traditional printed materials. They also expressed a desire for more varied and interactive learning methods. Based on these findings, developing an e-book with Canva is strongly recommended to make science learning more effective and to support students’ 21st-century skill development in elementary education.